Glutamic Acid Decarboxylase Autoantibodies Role in Reclassifying Diabetes of Adulthood in Basrah - Abbas Ali Mansour; Ammar Mohamd Saead Almomin; Ali Hussein Ali Alhamza (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2015)
Aim: To determine the prevalence and phenotypic characteristics of diabetes subtypes based on glutamic acid decarboxylase autoantibodies (GADA) status in those newly presented diabetic to the Al-Faiha Specialized Diabetes, Endocrine and Metabolism Center (FDEMC) in Basrah, Southern Iraq. Methods: The study design is cross-sectional and includes adult diabetic patients if they are free of insulin treatment for at least 6 months from diagnosis and to be 30 years of age and over from the period of January 2013 to March 2013. Results: Of our diabetics with age 30 years and more, 26.4% were GADA-positive. The only significantly higher variables seen more among GADA-positive diabetes groups were normal weight and current insulin uses. GADA-positivity was not associated with gender, age, BMI, family history, smoking, hypertension, duration of diabetes, or specific HbA1c in the current study. Conclusion: A quarter of adults diabetic in Basrah were GADA positive. GADA positivity means more likely to be normal weight diabetics and currently on insulin use.